THE CORRELATION BETWEEN HABIT OF WATCHING ENGLISH MOVIES AND VOCABULARY MASTERY OF THE TENTH-GRADE OF SMAN 1 KUTA SELATAN IN ACADEMIC YEAR 2020/2021 - Aliyatul Fikriyah; Dewa Ayu Ari Wiryadi Joni; Ida Ayu Made Sri Widiastuti (Academic Journal on English Studies (AJOES), 2021)
The objective of this study was to find out the significant correlation between students’ habit of watching English movies and vocabulary mastery of the tenth-grade of SMAN 1 Kuta Selatan in academic year 2020/2021. The sample of this research were 38 students of SMAN 1 Kuta Selatan. For collecting the data, there were two instruments used which were a questionnaire to find out the students’ habit of watching English movies and the multiple-choice test item for vocabulary mastery. The questionnaire used included aspects such as frequency, repetition, and automatic behaviour of habit of watching English movies, while the multiple-choice test item consisted of noun, verb, pronoun, and adjective. The SPSS 23.0 program was used to analyse the data. The result of Pearson Product Moment showed that the r-counted was 0.707. It lied between 0.600-0.800 which was in a sufficient level. It showed that there was a positive and significant correlation between students’ habit of watching English movies and vocabulary mastery of the tenth-grade of SMAN 1 Kuta Selatan in academic year 2020/2021.